2020
DOI: 10.1212/nxi.0000000000000682
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric autoimmune encephalitis

Abstract: ObjectiveThe aims of this study were (1) to describe the incidence of autoimmune encephalitis (AIE) and acute disseminated encephalomyelitis (ADEM) in children, (2) to validate the currently used clinical criteria to diagnose AIE, and (3) to describe pitfalls in the diagnosis of pediatric autoimmune (AI) and inflammatory neurologic disorders.MethodsThis study cohort consists of 3 patient categories: (1) children with antibody-mediated AIE (n = 21), (2) children with ADEM (n = 32), and (3) children with suspici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 27 publications
(39 reference statements)
0
33
2
4
Order By: Relevance
“…15 A retrospective cohort study by de Bruijn et al (2020) of 113 children diagnosed with AE showed the following characteristics: an incidence rate of 1.54 children/million, a female predominance, a median age of 14 years, and a presentation with seizures in 62% of cases. 16 Recommended investigations are as with other AE, and they should include brain imaging, EEG, and antibody testing in CSF and serum, in addition to investigations to rule out potential differential diagnoses (particularly other causes of inflammatory encephalitis). MRI and EEG findings tended to be nonspecific and occur in, but not limited to, the mesial temporal structures.…”
Section: Discussionmentioning
confidence: 99%
“…15 A retrospective cohort study by de Bruijn et al (2020) of 113 children diagnosed with AE showed the following characteristics: an incidence rate of 1.54 children/million, a female predominance, a median age of 14 years, and a presentation with seizures in 62% of cases. 16 Recommended investigations are as with other AE, and they should include brain imaging, EEG, and antibody testing in CSF and serum, in addition to investigations to rule out potential differential diagnoses (particularly other causes of inflammatory encephalitis). MRI and EEG findings tended to be nonspecific and occur in, but not limited to, the mesial temporal structures.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis and acute disseminated encephalomyelitis (ADEM) are the most frequently described forms of autoimmune encephalitis in children. In one study of 103 children with AES, 19 children had anti-NMDAR encephalitis and 34 children had ADEM [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
“…The approach was mainly based on experience with adult patients, although data from children were also taken in consideration for some diseases (e.g., anti-NMDAR encephalitis). To validate these algorithmic diagnostic guidelines in children, de Bruijn and colleagues 23 investigated 113 children that were initially included in 3 categories: (1) children with antibody-mediated encephalitis (n = 21), (2) children with acute disseminated encephalomyelitis (ADEM, n = 34), and (3) children with neurologic symptoms suspected to be autoimmune (n = 60). Overall, 103 children fulfilled the criteria of possible autoimmune encephalitis.…”
mentioning
confidence: 99%